MHP1, an essential gene in Saccharomyces cerevisiae required for microtubule function. - Irminger-Finger, Irmgard; Hurt, Ed; Roebuck, A.; Collart, M. A.; Edelstein, S. J. (The journal of cell biology, 1996)
The gene for a microtubule-associated protein (MAP), termed MHP1 (MAP-Homologous Protein 1), was isolated from Saccharomyces cerevisiae by expression cloning using antibodies specific for the Drosophila 205K MAP. MHP1 encodes an essential protein of 1,398 amino acids that contains near its COOH-terminal end a sequence homologous to the microtubule-binding domain of MAP2, MAP4, and tau. While total disruptions are lethal, NH2-terminal deletion mutations of MHP1 are viable, and the expression of the COOH-terminal two-thirds of the protein is sufficient for vegetative growth. Nonviable deletion-disruption mutations of MHP1 can be partially complemented by the expression of the Drosophila 205K MAP. Mhp1p binds to microtubules in vitro, and it is the COOH-terminal region containing the tau-homologous motif that mediates microtubule binding. Antibodies directed against a COOH-terminal peptide of Mhp1p decorate cytoplasmic microtubules and mitotic spindles as revealed by immunofluorescence microscopy. The overexpression of an NH2-terminal deletion mutation of MHP1 results in an accumulation of large-budded cells with short spindles and disturbed nuclear migration. In asynchronously growing cells that overexpress MHP1 from a multicopy plasmid, the length and number of cytoplasmic microtubules is increased and the proportion of mitotic cells is decreased, while haploid cells in which the expression of MHP1 has been silenced exhibit few microtubules. These results suggest that MHP1 is essential for the formation and/or stabilization of microtubules.